2000
DOI: 10.1034/j.1600-0420.2000.078006618.x
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprost‐induced increase of tyrosinase transcription in iridial melanocytes

Abstract: ABSTRACT.Purpose: Latanoprost, the active principle of Xalatan R eye drops, has been shown to cause increased iridial pigmentation as a side-effect in some patients. The purpose of the present study was to investigate whether latanoprost affects tyrosinase, the rate limiting enzyme in melanogenesis, at the gene transcription level in the iridial melanocytes. Methods: Four cynomolgus monkeys were treated unilaterally with 3 or 11 mg latanoprost once daily for 10 days. The contralateral eye received the vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…26 Latanoprost was found to affect tyrosinase at the gene transcription level in iridial melanocytes as observed in a comparison of treated and control cynomolgus monkeys. 76 This outcome was verified using human cultured iridial melanocytes from donors not previously treated with latanoprost, and further demonstrated that latanoprost can increase tyrosinase activity both in vivo and in vitro. Transcription of the tyrosinase gene in iridial melanocytes was selectively increased in mixed-color irides (hazel) but not in melanocytes from blue or brown irides.…”
Section: Iridial Pigmentationmentioning
confidence: 76%
See 1 more Smart Citation
“…26 Latanoprost was found to affect tyrosinase at the gene transcription level in iridial melanocytes as observed in a comparison of treated and control cynomolgus monkeys. 76 This outcome was verified using human cultured iridial melanocytes from donors not previously treated with latanoprost, and further demonstrated that latanoprost can increase tyrosinase activity both in vivo and in vitro. Transcription of the tyrosinase gene in iridial melanocytes was selectively increased in mixed-color irides (hazel) but not in melanocytes from blue or brown irides.…”
Section: Iridial Pigmentationmentioning
confidence: 76%
“…Transcription of the tyrosinase gene in iridial melanocytes was selectively increased in mixed-color irides (hazel) but not in melanocytes from blue or brown irides. 76 Increased expression of tyrosinase also was demonstrated in six of the 30 (20%) whole iris cultures from human donors. 75 Five of the six responders had brown eyes, and the remaining responder had hazel eyes.…”
Section: Iridial Pigmentationmentioning
confidence: 92%
“…[10][11][12][13][14][15][16][17][18][19] The PGF 2a -derivative-induced eye colour change is most likely due to an increased amount of melanin within iris stroma melanocytes. [20][21][22] These adverse effects may be related to the stimulation of prostanoid FP receptors in the eye. 3) To judge from the accumulating findings relating to latanoprost and other PGF 2a derivatives, prostanoid FP-receptor agonists are among the most promising ocular-hypotensive agents.…”
mentioning
confidence: 99%
“…8 Çeşitli çalışmalarla prostaglandinlerin hem tirozinaz gen transkripsiyonunu arttırarak hem de direkt tirozinaz enzim aktivitesini arttırarak melanogenezi arttırdığı, bunun da muhtemelen prostanoid reseptör uyarımı yolu ile olduğu gösterilmiştir. 2,8,[17][18][19][20] Elektron mikroskopisi ile yapılan çalışmalarda immatür melanozom ya da matür melanin granüllerinin sayısında değişiklik olmadan var olan melanin granüllerinin boyutunun arttığı gösterilmiştir. 8 PGA ilişkili iris hiperpigmentasyonu çoğunlukla tedavinin bitmesine rağmen düzelme göstermez veya çok yavaş gerileme gösterir.…”
Section: Pga-i̇ris Hiperpigmentasyonuunclassified